Tetraselmis chuii as a sustainable and healthy ingredient to produce gluten-free bread: impact on structure, colour and bioactivity - Nunes, Maria Cristiana (2020)
The objective of this work is to increase the nutritional quality of gluten-free (GF) bread by addition of Tetraselmis chuii microalgal biomass, a sustainable source of protein and bioactive compounds. The impact of di erent levels of T. chuii (0%—Control, 1%, 2% and 4% w/w) on the GF doughs and breads’ structure was studied. Microdough-Lab mixing tests and oscillatory rheology were conducted to evaluate the dough´s structure. Physical properties of the loaves, total phenolic content (Folin-Ciocalteu) and antioxidant capacity (DPPH and FRAP) of the bread extracts were assessed. For the low additions of T. chuii (1% and 2%), a destabilising e ect is noticed, expressed by lower dough viscoelastic functions (G’ and G”) and poor baking results. At the higher level (4%) of microalgal addition, there was a structure recovery with bread volume increase and a decrease in crumb firmness. Moreover, 4% T. chuii bread presented higher total phenolic content and antioxidant capacity when compared to control. Bread with 4% T. chuii seems particularly interesting since a significant increase in the bioactivity and an innovative green appearance was achieved, with a low impact on technological performance, but with lower sensory scores